Redimensionando a linguagem das histórias em quadrinhos para incluir a pessoa com deficiência visual - Barbosa, Ana Laura Campos (2021)
Information Science (IC) has sought to understand how information is used and understood in our society. With technological development, it gains an even broader dimension, enabling a greater number of people to have access to knowledge, including people with disabilities. Assistive Technology (AT) has contributed to provide ways of accessing information for these people. In the state of Sergipe, the Coordination of Educational Support for Persons with Disabilities (COEPD) is intended to help these individuals to be trained in appropriate technologies to interact with knowledge. Faced with the debate on social inclusion and the construction of a more inclusive society, we highlight the language of comic books, a cultural asset that is widely used, but not very accessible to the blind person. Thus, this study has as general objective to understand the contribution of AT for the visually impaired person to have access to the language of Comics with autonomy. As a methodology, a qualitative approach with a focus on phenomenology was used, and an exploratory study was carried out, from the perspective of participant research, having the COEPD as the universe. We conclude that the Comics can become accessible to the blind public using resources made possible by AT, as well as Braille writing, high relief printing and image description, using the accessibility proposal based on universal design for reading shared, if possible, to all human diversity